Pembaharuan Hukum : Reformasi Sistem Peradilan Militer di Indonesia - Irman Putra; Arief Fahmi Lubis (Public Service and Governance Journal, 2020)
Reform of the military justice system (criminal law enforcement) is essentially part of the idea of law reform. Legal reform includes not only "legal substance reform" and "legal structure reform", but also "legal culture reform". Therefore, the reform of the military criminal law system must also be accompanied by the renewal of the military legal culture, which includes, among other things, the renewal of the cultural aspects of legal behavior and legal awareness related to "military culture" and the renewal of the aspect of military legal education/science. So, "legal behaviour, legal, science and legal education reform" is also needed. This research will discuss Military Justice Reform in Indonesia, by conducting a comparative study with the existing military justice systems in various countries. This article concludes that the prospect of the position of the military court in Indonesia after the administrative, organizational, and financial fields are in the Supreme Court will make the military court better and more independent. The administration and organization will be more well organized in accordance with other courts.